Molecular detection of efflux pump genes in clinical isolates of MDR Pseudomonas aeruginosa - Muslim M. Kadhim; Aseel R. Mardan (Advancements in Life Sciences, 2026)
Background: Pseudomonas aeruginosa is an opportunistic pathogen and a leading cause of various infections, including community-acquired and healthcare-associated infections. This organism is highly resistant to different classes of antimicrobials through multiple mechanisms, presenting a major challenge for infection treatment in hospital settings. Therefore, this study aimed to detect RND-type efflux pump genes, including mexAB, mexXY, mexC, and oprM, in multi-drug resistant (MDR) P. aeruginosa clinical isolates from Diyala Province using PCR technology.Methods: A total of 50 clinical isolates were recovered from patients with different infections between November 2022 and March 2023. Twenty MDR isolates were selected based on antimicrobial susceptibility testing and subsequently confirmed using the VITEK 2 Compact system. Demographically, the isolates were obtained from 23 males (46%) and 27 females (54%). Twenty MDR isolates were selected based on antimicrobial susceptibility testing against 10 distinct antimicrobials using the Kirby-Bauer disk diffusion method.Results: Molecular screening revealed that 10/20 (50%) of the isolates harbored the mexB gene, while the mexA gene was not detected in any isolate (0/20, 0%). Notably, all isolates carried both the mexC and mexY genes (20/20, 100%). Furthermore, 2/20 (10%) of the isolates harbored the mexX gene, whereas only 1/20 (5%) was positive for the oprM gene.Conclusion: The current study showed in conclusion a rise in the spread of Mex efflux pump genes between the MDR isolates of P. aeruginosa bacteria that we obtained from different clinical samples in Diyala province, and therefore the isolated positive efflux pumps were detected in this study and this indicates the extent of enhanced prevention and severe control of this infection.Keywords P. aeruginosa, Antimicrobial resistance, MDR, Efflux pump genes